Genetic Algorithm Assisted Optimum Detection For Block Data Transmission Systems - Babu, Shanmugaih Palanichamy Kulandaivel (2010)

(untitled)
Recent years have witnessed an increase in demand for higher transmission data rates for wireless multimedia communications applications. Wireless data transmission systems with high data rates always face problems over time dispersive channels. New technologies that employ block data transmission where the data is converted into blocks separated by known symbols have been introduced to combat the impairments due to dispersive channels. This arrangement confines the Inter Symbol Interference (ISI) to a particular block and allows Block-by-Block data processing. Block Data Transmission Systems (BDTS) is one of the promising techniques for high data rate data transmission and found in the fourth generation wireless technologies such as Orthogonal Frequency Division Multiplexing (OFDM), Single Carrier Frequency Division Multiple Access (SC-FDMA) and Discrete Multi Tone (DMT) Modulation schemes etc.